KONSEP PENDIDIKAN ORANG DEWASA - Sunhaji Sunhaji (Jurnal Kependidikan)
Advances in science and technology today, the one that needs attention is the concept of education for adults . Not always we talk and review the student's educational sputar school in the relatively young age of the reality on the ground , that is not little adults who should receive education , both informal and non -formal education , for example in the form of skills , courses , refresher courses and so on . The problem that often arises is how to tips and strategies membelajarkan adult postscript school is not occupied . In pskologis adults as students in learning activities can not be treated like regular students children who were sitting in the school . Adults grow as a person and have a maturity of self-concept moves from dependency as occurs in childhood toward independence or self-direction . Adult psychological maturity as a person capable of self-directed and not directed, forced and manipulated by others.